PENGARUH PEMBELAJARAN RECIPROCAL TEACHING DIPADUKAN THINK PAIR SHARE TERHADAP PENINGKATAN KEMAMPUAN METAKOGNITIF BELAJAR BIOLOGI SISWA SMA BERKEMAMPUAN AKADEMIK BERBEDA DI KABUPATEN SIDOARJO - Nur Effendi (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2013)
In the globalization era, the world is developed without the boundary, the development of the sciences and technologies have been needed by people in the nation, to increase the quality of education. In the biology (sciences) has been needed to adapt student-centered learning paradigm than the teacher-centered. The purposes of the study are to apply the Reciprocal Teaching (RT), Think Pair Share (TPS), Reciprocal Teaching Plus Think Pair Share (RT+TPS) learning strategic to increase the metacognitive ability in learning biology for the senior high school students in Sidoarjo with different academic capability. The study is a quasi experiment. The research design is pre-post test non-equivalent control group design with the 4x2 factorial pattern. The total sample is 240 students. Data are subjected to the ANACOVA statistic and followed by the LSD test with 0.05 significance degree. The result of inferential analysis indicates that the learning strategy and academic capability influenced the metacognitive ability students. The average score metacognitive ability remarks in the RT+TPS with remarks 77.73 and the higher 1.65% than TPS with remarks 76.44, but the really different and the higher 2.92% than RT with remarks 75.45, 4.33% than the Conventional with remarks 74.36. The average score met cognitive ability remarks Up students academic capability performs is 76.53 is the really different and the higher 1.39% than the Down student academic capability performs is 75.46. The average score RT+TPS strategy learning in the Up academic capability with the remarks 78.93 and the higher 1.42% than TPS-Up academic with remarks 77.82, but the really different and the higher 4.86% than RT-Up academic with remarks 75.10, 5,91% than the Conventional-Up academic with remarks 74.27. The average score metacognitive ability strategy learning RT+TPS-Up academic is really different and higher 3.05% than RT+TPS-Down academic with remarks 76.53. The RT+TPS strategy learning application have the best result to increase the metacognitive ability in learning biology if it is compared with the RT, TPS, or Conventional strategy learning on the Up or Down students academic capability performs. This strategy can be used for the largest biology learning and as the alternative to manage the instruction learning in the class, the factor fundamental to make decision for the stake holders, and the first research for the references continuous research.